Synthesis, Biological Evaluation, and Molecular Docking of (R)‐2‐((8‐(3‐aminopiperidin‐1‐yl)‐3‐methyl‐7‐(3‐methylbut‐2‐en‐1‐yl)‐2, 6‐dioxo‐2, 3, 6, 7‐tetrahydro‐1H‐purin‐1‐yl)methyl)benzonitrile as Dipeptidyl Peptidase IV Inhibitors. (23rd November 2015) - Ran, Yan; Pei, Heying; Shao, Mingfeng; Chen, Lijuan
Abstract : Type 2 diabetes (T2D) is classified as a major metabolic disorder, which has affected approximately 194 million people worldwide. DPP‐IV inhibitors as a new therapy have shown several advantages over traditional antidiabetic drugs. Based on the similar binding modes of Alogliptin and Linagliptin, molecular operation was conducted via combining pharmacophore hybridization with structural optimization between the two market drugs and racemic compounds40 and43 were reported as DPP‐IV inhibitors in our previous studies. But the majority of DPP‐IV inhibitors have developed into a small molecule with certain conformation; in this study, we described the synthesis, biological evaluation, and molecular docking of corresponding enantiomers of compounds40 and43 . The most potent inhibitor is(R)‐40 (IC50  = 23.5 nm, F  = 74.67%, T 1/2  = 4 h), which exhibited moderate antihyperglycemic activity as compared to the standard antidiabetic drug Linagliptin in OGTT. In addition, compound(R)‐40 effectively improved the pathological state of DIO mice. Molecular docking studies clarified the favorable binding affinity between compound(R)‐40 and DPP‐IV active site. Thus, compound(R)‐40 would be entitled to further development as a drug candidate on the basis of the suitable pharmacokinetic (PK) and desirable pharmacodynamic (PD) profiles. Abstract : In this paper, we described the synthesis, biological evaluation and molecular docking of corresponding enantiomers of compounds40 and43 . The most potent inhibitor is(R)‐40 (IC50 = 23.5 nM, F = 74.67%, T1/2 = 4 h), which exhibited moderate antihyperglycemic activity as compared to the standard antidiabetic drug Linagliptin in OGTT. In addition, compound(R)‐40 effectively improved the pathological state of DIO mice. Molecular docking studies clarified the favorable binding affinity between compound(R)‐40 and DPP‐IV active site.